Rib soft fixation produces better analgesic effects and is associated with cytokine changes within the spinal cord in a rat rib fracture model. (June 2019) - Liu, Yuan-Yuarn; Wang, Jeffrey Chi-Fei; Lin, Ya-Chi; Hsiao, Hung-Tsung; Liu, Yen-Chin
Traumatic rib fracture can cause severe pain and is usually associated with the depression of respiratory drive followed by severe respiratory complications. It is critical for patients with rib fracture to receive adequate analgesia. However, strong opioids and other analgesics often produces side effects and may even cause respiratory suppression. Meanwhile, rib fixation now has become a popular method for treating rib fracture patients. However, the actual molecular mechanism leading to its effectiveness as an analgesia has not been fully investigated, and the best analgesic method for its use in rib fracture patients has not yet been determined. We developed a new animal model for rib fracture and evaluated changes in pain severity after rib fixation. Our data indicated significantly better analgesic behavior if a soft string rib fixation is performed, which is associated with cytokine (interleukine-6 and interleukine-10) decreases in the spinal cord and co-localization with glia cells. Our results provided a treatment suggestion for rib fracture patients and the possible molecular mechanism for the analgesic effects. Further molecular mechanisms and the best therapeutic methods are still needed for this severe painful condition.